Simplicity and Commutative Bases of Derivations in Polynomial and Power Series Rings. (12th December 2013) - Baltazar, Rene
Abstract : The first part of the paper will describe a recent result of Retert in (2006) for k x 1, …, x n and k x 1, …, x n . This result states that if 𝔇 is a set of commute k -derivations of k x, y such that both ∂ x ∈ 𝔇 and the ring is 𝔇 -simple, then there is d ∈ 𝔇 such that k x, y is ∂ x, d -simple. As for applications, we obtain relationships with known results of A. Nowicki on commutative bases of derivations.